HUBUNGAN HASIL BELAJAR DARING DENGAN MINAT DAN MOTIVASI BELAJAR MAHASISWA DI ERA PANDEMI COVID-19 - Wiwin Apriani; Nurhayati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2021)
The distance learning process is something new for students, so there needs to be an adaptation for students so that they can learn well and can absorb the material given well. Therefore, this study will analyze the percentage of interest level and motivation to learn mathematics of mathematics education study program students at Almuslim University during the Covid 19 pandemic. The method used is a case study qualitative research with a population of all students of the Almuslim University mathematics education program. Data collection techniques are using a questionnaire of student interest and learning motivation and interviews. The results obtained were that the average interest and motivation of students in taking online lectures was 66.8%. Then the average student learning outcomes during online learning was 82.36%, this indicates that the learning outcomes of the Al-Muslim University Mathematics Education Study Program students were in a good category. So it can be concluded that if the students' interest and motivation are good, it will also increase the learning outcomes obtained. The relationship between online learning and student learning interest and motivation shows a strong relationship, which is 66.1%. In addition, the relationship that the online learning process has with student interest and learning motivation shows a positive relationship, which means that if the online learning process increases better, student interest and learning motivation will also increase.